A two-stage stochastic optimization model for reverse logistics network design under dynamic suppliers' locations. (15th July 2019) - Trochu, Julien; Chaabane, Amin; Ouhimmou, Mustapha
Highlights: A two-stage stochastic model for reverse logistics network design is developed. The collected volume and the recycling rates at the collection centers are uncertain. Our model considers joint dynamic supply sources and source separation centers. A case study targeting waste management in the (*CRD: Construction, Renovation and Demolition) industry is presented. The benefits of source separation for waste management efficiency is highlighted. Abstract: This paper presents a two-stage stochastic programming model for reverse logistics network design (RLND) under uncertainty with dynamic supply sources' locations. The primary objective of the optimization model is to maximize the expected profit generated by selling recycled materials to the secondary markets and to make the landfilling option less attractive. In comparison with the state-of-the-art stochastic optimization models in this area, which mainly focus on the expected optimal value, this paper emphasizes the role of source separation of recyclable materials to increase the productivity level at the collection centers (CC). Indeed, the quantity of materials collected from the supply sources and the recycling rates at the CC are the primary sources of uncertainty considered in this study. A Sample Average Approximation (SAA) procedure is developed to solve the stochastic model and perform sensitivity analyses on the number of supply sources, the sample size and the level of uncertainty targeting the random parameters. Managerial implications are discussed through a case study from the demolition industry in the province of Quebec, Canada. Although the use of source separation centers (SSC) improves the network performance in both rural and urban zones, the additional flexibility provided by these platforms reaches its best efficiency in the case of high-density urban areas. Finally, the results suggest significant RLND adjustments that lead to an increase in the average profit by 17.6% and recycle around 29% of additional building materials waste from demolition.